THE BEAK AND MORPHOMETRY OF THE BIGFIN REEF SQUID Sepioteuthis lessoniana LESSON IN EASTERN INDONESIAN SEAS - Abdul Ghofar (JOURNAL OF COASTAL DEVELOPMENT, 1997)
The study aims to investigating the morphometric and beaks relationships in the Bigfin reef squid, Sepioteuthis lessoniana Lesson 1830. It is shown that fin length and tentacle length linearly correlates with dorsal mantle length. Unlike fin-mantle relation which exhibits no sexual differences, tentacle tends to develop relatively more rapidly in female when mantle attains 70 mm. It is also evident that dorsal mantle length linearly correlates with lower hood length, with slope (b) and intercept (a) of 30.3 and 4.57, respectively. Logarithmic relationship is found between total body weight and lower hood length, with corresponding values of 2.84 and 0.611. Their application for coastal cephalopod biomass estimation from beaks is discussed.